2020
DOI: 10.1002/chem.202003240
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Bis‐alkylidene Complexes of Titanium and Zirconium: Synthesis, Characterization, and Reaction

Abstract: DedicatedtoProf. Pierre H. Dixneuf for his great contribution to the good friendship between the Chinese and French chemistry communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Cyclic bis-alkylidene titanium complex 1 was synthesized according to the published procedures. 10 Other commercially available reagents were used without purification.…”
Section: General Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic bis-alkylidene titanium complex 1 was synthesized according to the published procedures. 10 Other commercially available reagents were used without purification.…”
Section: General Remarksmentioning
confidence: 99%
“…9 As an extension of our work, we continue to expand this field to prepare the corresponding titanium hydrides and explore their reactivities with N 2 gas. In this work, by hydrogenating titanacyclopentatriene complex 1 , 10 stemming from the 1,4-dilithio-1,3-butadiene precursor, we obtained Ti-hydride complex 2 , {[(2-butene)(C 5 H 5 )Ti](μ-H) 2 Li(THF) 3 }. The subsequent reaction of 2 with dinitrogen led to the formation of Ti-N 2 complexes 4 and 5 , {[((2-butene)(C 5 H 5 )Ti) 2 (μ 2 -η 1 ,η 1 -N 2 )][Li(THF) 4 ]} and {[(2-butene)(C 5 H 5 )Ti] 2 (μ 2 -η 1 ,η 1 -N 2 )}, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Although neutral N,N-chelated spiro copper complexes are relatively common, the anionic C,N- or C,C-cheated spiro counterparts are sporadic. As mentioned above, Xi’s group found that the C,C-bidentate ligand is an excellent platform to build up diversified coordination complexes across the periodic table [ 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The chelating effect increases the thermal stability of these organometallic species, facilitating isolation and following characterization.…”
Section: Mononuclear Organocopper Complexesmentioning
confidence: 99%